Sistem Informasi Lembaga Pembinaan Khusus Anak Kelas II Tomohon Berbasis Web - Tirsa Kaunang; Jonathan Wijaya; Sondy Kumajas (JOINTER : Journal of Informatics Engineering, 2020)
Abstract—Correctional Information is public information that is produced and managed by the Directorate General of Prisons, region offices, and correctional technical units related to the administration of prisns in accordance with the provisions of the invitation and other information relating to the public interest. It is obligatory to present correctional information, expecially in LPKA Class II Tomohon, which is still manual, where people who want to see correctional information must come to LPKA Class II Tomohon. Therefore, a web-based information system was created which makes it easy to convey correctional information and also helps in submitting complaints. The research method used in this system is the waterfall which consists od analysis, design, code, and testing. The system modeling tool used is UML and testing uses the blackbox testing method.